2022
DOI: 10.3390/pr10071319
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Research on Drainage Structure of Highway Tunnel Based on Reducing the Risk of Crystallization Blockage

Abstract: Crystal blockages of tunnel drainage systems severely undermine the tunnel lining structure and operation safety. In order to reduce the risk of crystal blockages of tunnel drainage systems, the distribution of highway tunnel defects was identified through a field survey, indoor test, and literature analysis, and an optimization method of tunnel drainage structures was proposed. The research suggested the following: (1) Lining water leakage and construction joint water leakage were the most common defects in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Figure 1 depicts the crystallisation that was created at various locations in the tunnel. It has been shown that lining leakage and construction joint leakage are the most common defects in most highway tunnel drainage systems and that the subsurface water is mainly alkaline, with Ca 2+ (107 mg L −1 ) being the cation with the highest ion concentration and HCO 3 − being the anion with the highest ion concentration 3 . In the field of tunnelling, many studies on karst have been reported 4–6 ; Tao 7 discovered that dolomite contains CaO, MgO, Al 2 O 3 and other substances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 depicts the crystallisation that was created at various locations in the tunnel. It has been shown that lining leakage and construction joint leakage are the most common defects in most highway tunnel drainage systems and that the subsurface water is mainly alkaline, with Ca 2+ (107 mg L −1 ) being the cation with the highest ion concentration and HCO 3 − being the anion with the highest ion concentration 3 . In the field of tunnelling, many studies on karst have been reported 4–6 ; Tao 7 discovered that dolomite contains CaO, MgO, Al 2 O 3 and other substances.…”
Section: Introductionmentioning
confidence: 99%
“…À being the anion with the highest ion concentration. 3 In the field of tunnelling, many studies on karst have been reported [4][5][6] ; Tao 7 discovered that dolomite contains CaO, MgO, Al 2 O 3 and other substances. Xie and Rao et al 8,9 conducted an experimental study on the composition of dolomite and found that the main component of dolomite is CaCO 3 and contains MgO and Al 2 O 3 , which have a great influence on the physical properties of dolomite.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2018) studied the causes of water seepage in highcold tunnels and developed new tunnel drainage structures to optimize their layout. In addition, Liu et al (2022) investigated the distribution of defects in highway tunnels through on-site investigation, indoor experiments, and literature analysis to propose optimization methods for tunnel drainage structures to reduce the risk of crystal blockage in tunnel drainage systems. Ji et al (2012) suggested connecting the circular drainage pipe directly to the central drainage pipe and installing a strip insulation layer in areas with water-rich surrounding rocks and where the middle and lower parts of the circular drainage pipe are prone to freezing.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 16 introduced the basic principles, ideas, and specific measures for the treatment of diseases such as water leakage, insulation, and lining reinforcement in the Dabanshan cold Tunnel by analyzing the causes of the diseases of tunnels. To reduce the risk of blockage in the tunnel drainage system, Liu et al 17 determined the distribution of defects in highway tunnels through on-site investigation, indoor experiments, and literature analysis, and proposed an optimization method for tunnel drainage structure. Ji et al 18 proposed that the circular drainage pipe should be directly connected to the central drainage pipe, and a strip insulation layer should be installed in areas where the surrounding rock is rich in water and the middle and lower parts of the circular drainage pipe are prone to freezing.…”
Section: Introductionmentioning
confidence: 99%